2021
DOI: 10.1002/eat.23626
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral reinforcement of pathological exercise in anorexia nervosa

Abstract: Pathological exercise in anorexia nervosa (AN) is a harmful behavior associated with a chronic course and poor prognosis. To date, no comprehensive theoretical model exists to describe pathological exercise in the context of AN, and as such, few treatments are effective at promoting direct and sustained pathological exercise extinction.Using a framework put forth by Wise & Koob (2014), debating the relative importance of positive and negative reinforcement in substance use, we present three hypotheses of behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 94 publications
2
13
0
Order By: Relevance
“…This suggests that lack of exercise enjoyment might not be relevant in compulsive exercise for AN and BN. Furthermore, recent theoretical proposals also suggest improving models for a better understanding of compulsive exercise in EDs (e.g., Coniglio, Cooper, & Selby, 2022; Kolar & Gorrell, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that lack of exercise enjoyment might not be relevant in compulsive exercise for AN and BN. Furthermore, recent theoretical proposals also suggest improving models for a better understanding of compulsive exercise in EDs (e.g., Coniglio, Cooper, & Selby, 2022; Kolar & Gorrell, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, these validation studies did report positive correlations between physical exercise addiction symptoms and eating disorder symptoms (for the EDS and CET; the EAI did not include such measures). It is thus likely that even when what is measured by such scales is genuinely problematic, it is impossible to ascertain that what is measured is not just a potentially maladaptive strategy displayed to cope with symptoms of an eating disorder ( Bamber, Cockerill, Rodgers, & Carroll, 2000 , 2003 ; Coniglio, Cooper, & Selby, 2021 ). Such an account is in line with data showing that the association between physical exercise addiction and reduced quality of life does not hold after statistically controlling for the effects of eating disorder psychopathology ( Mond, Hay, Rodgers, & Owen, 2006 ).…”
Section: Validity Problems In Exercise Addiction Measurementmentioning
confidence: 99%
“…Intervention studies can also serve to provide evidence for and against particular mechanisms. For example, Coniglio et al (2021) indicated that if compulsive exercise is best explained as a habit maintained by positive and negative reinforcement, then habit reversal training may be an effective treatment. The recent interest in ketamine therapy for obsessive-compulsive disorder (OCD), substance use disorders, and eating disorders is a clear example of how we can leverage mechanistic studies to augment existing treatment.…”
Section: Enhancing Existing Interventions Informed By Mechanistic Res...mentioning
confidence: 99%